Impact of management technologies on banana growth and fusarium wilt mitigation - Doyal, S; Kavitha, P S; Muthuvel, I; Sudha , A; Vanitha , K (Plant Science Today, 2025)
The study was conducted during 2023-2024 under the Department of Fruit Science, Horticultural College and Research Institute, Tamil Nadu Agricultural University, Coimbatore. The objective of the study was to find out the best technology for the Fusarium wilt management in the banana cultivar Rasthali under pot culture experiment. The experiment was conducted with nine treatments replicated thrice with three plants in each replication in a completely randomized design (CRD). The treatment T7- Bacillus subtilis (10 g/plant) +Salicylic acid 5mM spray showed more root length (71.89 cm) and number of roots (30) than other treatments. The treatment T7- Bacillus subtilis (10 g/plant) + Salicylic acid 5mM spray showed a 33 % improvement in root length over absolute control (T1) and a 53 % increase over inoculated control (T2). Whereas the number of roots was 50% more in T7 than in T1 and 76 % more than in T2. The length of the pseudostem and girth of the pseudostem were 69.40 cm and 25.43 cm. The leaf area was 2.99 m2 and the number of leaves was 12. The physiological parameters such as chlorophyll content (57.03), stomatal resistance (0.521 Scm-1) and transpiration rate (9.572 ?g H2O cm2 S-1) of T7 were significant. In soil enzymes, the chitinase activity was 37.50 ?mol/min/g and ? 1, 3 Glucanase 40.33 ?mol/min/g. It showed less disease incidence (DI %) of 18.86 % and a disease severity index (DSI %) of 14.73 %. The absolute control (T1), without the pathogen, had no disease. The inoculated control (T2) showed the highest disease incidence and disease severity index of 100 %. T7- Bacillus subtilis (10 g/plant) + Salicylic acid 5 mM spray showed less disease incidence (DI %) of 18.86 % and a disease severity index (DSI%) of 22.93 % over the absolute control (T1). And 81.14 % and 77.07 % reduced disease incidence (DI %) and disease severity index (DSI %) compared to inoculated control (T2). It is concluded that T7- Bacillus subtilis (10 g/plant) + Salicylic acid 5 mM spray can be used to control Fusarium wilt in cultivar Rasthali.